Analisis Faktor-Faktor yang Memengaruhi Pilihan Konsumen terhadap Produk dan Layanan Keuangan Syariah - Eriana Huzein Arif (EKALAYA : Jurnal Ekonomi Akuntansi, 2026)
The development of the Islamic financial industry in Indonesia has experienced significant growth in recent years. This condition is influenced by increasing public awareness of sharia principles in economic and financial activities. This study aims to analyze the factors influencing consumer choices toward Islamic financial products and services. The research method used is a literature study by reviewing various scientific journals, books, and academic articles related to consumer behavior in choosing Islamic financial services. The results indicate that religiosity, service quality, trust, knowledge of Islamic finance, accessibility, and social influence are the main factors affecting consumer decisions. In addition, institutional image and digital innovation also play an important role in increasing public interest in Islamic financial products. This study concludes that Islamic financial institutions need to improve education, service quality, and technological innovation to compete with conventional financial institutions.